An Elevated METS-IR Index Is Associated With Higher Asthma Morbidity and Earlier Age of First Asthma in US Adults: Results Based on a Cross-Sectional Study - Chen, Yan; Yang, Junping; Han, Kexing; Wang, Yan; Zhuang, Cuixia; Zhu, Laxiang; Chen, Mingwei (Frontiers in Endocrinology, 2022)
Objective：The purpose of this study was to evaluate whether there is a correlation between the METS-IR index and asthma among Americans. Methods：In an attempt to establish the relationship between the METS-IR index and asthma prevalence and age at first onset of asthma, we conducted a logistic regression analysis, subgroup analysis, and dose-response curve analysis using the National Health and Nutrition Examination Survey (NHANES) database. Results：Based on analysis after adjustment for all confounders, each unit increase in METS-IR index led to 1.2% increase in asthma incidence (OR= 1.012, 95% CI: 1.01, 1.014) and an earlier age of onset of asthma by 0.04 years (β= -0.040, 95% CI: -0.078, -0.003).A stratified analysis determined that METS-IR index increases were related to asthma onset across all subgroups, and a positive nonlinear correlation was found between METS-IR index and asthma onset. The threshold saturation effect analysis found inflection points at 42.695 and 73.413, but with a linear negative correlation between METE-IR index and age of first asthma onset. Conclusion: Despite the fact that a direct causal relationship cannot be demonstrated, a higher METS-IR index is positively related to asthma incidence and correspondingly may result in asthma onset at younger ages.